Sea-coast Tourism Activity in Romania during the Pandemics (Analele Universității București.Geografie, 2025)
The presence of the Covid 19 pandemic on the Romanian territory involved different stages and intensities of manifestation in terms of both space and time. The decrease in tourist travel has affected the proper functioning of the entire HORECA system. In addition, the implementation of the measures meant to limit the spread of the virus has greatly reduced the flow of tourists who accounted for the main forms of tourism. The tourism restrictions put in place triggers the need for rethinking the sea-coast tourism, which is one of the most popular among Romanian tourists. The main issue in this regard is the need for establishing a physical distance of two meters between people. Since the number of sea-coast located accommodation units is lower than the total number of accommodation units this translates into the fact that not all accommodation units would be able to benefit from the presence of tourists on the beach, along with the reduction of the existing congestion that is present every year in the summer season.All the documentation studies underpinning this paper show that the Romanian sea-coast tourism is focused on a short, very crowded season, and that the use of the beach areas should be reconsidered, keeping in mind the objective of improving tourist services. The lesson that the pandemic teaches us is that it is possible to generate a high-quality tourism consisting in ensuring an increased comfort, with a smaller number of tourists, by extending the up- season to four months.